1997
DOI: 10.1046/j.1365-2265.1997.1110923.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of thyroid stimulating activity within H chain fragments of TSAb‐IgG by protease digestion and reduction

Abstract: The thyroid stimulating activity in 5 TSAb-IgG samples was found in IgG(kappa), IgG(lambda), Fab(kappa), Fab(lambda), H chain and Fd separated by papain digestion and reduction. These results showed that TSAb was polyclonal and that the Fd fragment was important as the biologically active site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently, we demonstrated that the TS activity in TSAb-IgG hydrolysed with papain is located in not only the Fab fragment but also in the fraction containing much smaller components (Ogura et al, 1995). Furthermore, we identified TS activity in the free H chain and the Fd fragment of TSAb-IgG molecule using papain digestion and reduction (Kouki et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we demonstrated that the TS activity in TSAb-IgG hydrolysed with papain is located in not only the Fab fragment but also in the fraction containing much smaller components (Ogura et al, 1995). Furthermore, we identified TS activity in the free H chain and the Fd fragment of TSAb-IgG molecule using papain digestion and reduction (Kouki et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Sera in this study showed between 25% and 87% TBII activity (standard method). Thyroid stimulating antibody (TSAb) activity was determined by a commercial TSAb assay kit (Yamasa Co., Choshi, Ciba, Japan) (Kouki et al. , 1997a).…”
Section: Methodsmentioning
confidence: 99%
“…Sera in this study showed between 25% and 87% TBII activity (standard method). Thyroid stimulating antibody (TSAb) activity was determined by a commercial TSAb assay kit (Yamasa Co., Choshi, Ciba, Japan) (Kouki et al , 1997a). Thyroid blocking antibody (TBAb) activity was determined by the incubation of test IgG in the presence of 25 µ U of bTSH using this kit as described previously (Kouki et al , 1997b).…”
Section: Thyroid Function Testsmentioning
confidence: 99%
“…The IgG was digested by papain+ cysteine or pepsin. The unbound fraction of Protein A-column was gel-filtrated on Sephadex G-100 column and obtained Fab and F(ab') 2 fragments as described previously [7,8].…”
Section: ) Test Sera and Igg Fractionmentioning
confidence: 99%